UPAYA PENYIDIK SATUAN RESERSE KRIMINAL POLRES PESISIR SELATAN DALAM MENENTUKAN TEMPAT KEJADIAN PERKARA TINDAK PIDANA PEMBUNUHAN - Can, Nofrizal (Ensiklopedia Sosial Review, 2020)
According to Article 7 of the Criminal Procedure Code, investigators have the authority to handle reports of suspected criminal events. Investigators are also obliged to carry out examinations at the scene of the crime. As in the Police report Number: LP / 61 / K / IX / 2017 / Sek-str, dated 18 September 2017, there has been a criminal offense against a person's soul or a murder in Kampung Pasar Ajalai Sungai Sirah, Pesisir Selatan Regency. The problem that occurs is that investigators have obstacles in determining the scene of the crime of murder. This research is a descriptive analytical study. The approach used in this study is a normative juridical approach supported by an empirical juridical approach. The data used in this study are secondary data and primary data. All data and materials obtained from the research results were analyzed qualitatively, and presented in a qualitative descriptive form. Based on the discussion and analysis, it can be seen that: First, the efforts of investigators of the Criminal Investigation Unit of the Pesisir Selatan Police to determine the scene of the murder crime case are to process the scene of the crime and listen to the statements of witnesses who saw, heard and knew about the crime, and the investigator brought expert witnesses to reinforce the elements of the crime the suspect has committed. Second, the obstacle for investigators of the Criminal Investigation Unit of the Pesisir Selatan Police in determining the scene of the murder case is that the suspect is not cooperative, the witnesses do not want to be questioned, the witnesses arrive late when asked for information, bring in expert witnesses, it takes a long time to bring in. Evidence is difficult to find and it is difficult to determine the scene of a criminal case, because the scene of the case varies.